THE RELATIONSHIP BETWEEN OIL REVENUES AND REAL NON – OIL GROSS DOMESTIC PRODUCT CONSIDERING FINANCIAL DEVELOPMENT IN IRAQ FOR THE PERIOD 1998_2023 (World Economics and Finance Bulletin, 2026)
The research aims to test the impact of the oil rent on the non-oil economic development in Iraq and also examine the mediating role of the financial development as a threshold variable of the same correlation. To gauge financial development of the Iraqi economy three indicators are chosen and one of them is a ratio of credit to the private sector, another ratio of liquidity to the GDP and last ratio of bank credit to the GDP. One of these indicators was carried out in the form of the Principal Component Analysis (PCA) to prevent the problem of the collinearity and inabilities of one indicator. A long Solow neoclassical growth model that included the index was included in the model which is a financial development and the variables of oil resources. The tests on the time series of 1998192023 data sets involved the stationarity and cointegration tests and threshold regression model. A series of diagnostic test was also addressed to make sure that the results were valid. The estimation was done in EViews and Stata. The results indicated that the economic time series variables of Iraq have non-stationary and stationary components of the time period between 19982023 since some of the variables are stationary at the level like LnYIRAQ or LnFDIRAQ, and stationary after initial differentiation like LnYIRAQ or LnFDIRAQ. In the four approximated threshold regression models, to find out the impacts of the various financial development indicators there is no significant effects observed on both the capital and the labor variable in relation to the non- oil growth which is an indication that Iraq is very much organized in its reliance on oil and that institutions are weak. This was the same case with oil rent, but the effect was not significant and was statistically positive (with the exception of the third model) at the lower levels of financial development. Conversely in cases where the financial development was high then the effect of oil rent was turned to the negative side and in certain models the effect was of great magnitude (especially in the third and fourth models). Diagnostic tests that included residual tests, Portmanteau tests and CUSUM tests were used to observe the stability of the models and good fit with an exception of the fourth model where the heteroscedasticity was experiencing. This was abolished with high standard errors that also added to the negative impact of the oil rent. Overall, the results indicate that the increase of the negative impacts such as the resource curse and Dutch disease cannot be avoided even in the modern situation when the financial indicators exceed the quantitative limits unless the quality and efficiency of resources allocation in the form of an institution is improved.